DOES THE INCREASE IN COFFEE PRICES INCREASE INDONESIAN COFFEE IMPORTS? - Ulil Albab (Journal of Applied Economics in Developing Countries, 2026)
This research examines the extent to which escalating global coffee prices influence Indonesia's coffee import behavior by analyzing the interplay of macroeconomic variables and industrial demand. Utilizing monthly time series data spanning from January 2018 to May 2025, the investigation employs an Autoregressive Distributed Lag (ARDL) model to delineate both short-run and long-run dynamics. The findings indicate that, in the short term, coffee imports diminish as a consequence of inflation and depreciation of the exchange rate, which is indicative of traditional cost-based adjustments. Conversely, in the long term, episodes of increased coffee prices correlate with a notable surge in imports. This trend suggests that Indonesia’s coffee import activities are motivated less by price deterrents and more by structural demand forces, particularly domestic supply limitations and ongoing processing requirements. The results imply the presence of imperfect price transmission and derived import demand within Indonesia’s coffee market, indicating that the dual function of the nation as both an exporter and importer may underscore inherent rigidity in domestic supply capabilities rather than solely market-driven trade reactions.